The Image Structure of the “Road” Theme in Rubtsov’s Poetry - Кудрявцев, М. В. (Kalbotyra, 1981)
The poetry of Nikolaj Rubtsov, a major contemporary Russian poet, has not so far been subjected to linguistic analysis. The present article deals with the semantic realization of one of the keythemes in Rubtsov’s poetry – the “road” theme. Rubtsov’s poetic system is characterized by a limited number of keythemes which remain constant throughout his works. Traditional symbols in Rubtsov’s poetry acquire a variety of contextual meanings. The structure of the “road” theme can be viewed as a paradigm of the main image motifs.